Suggested Method for Encryption and Hiding ‎Image using LCG and LSB (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Maintaining the confidentiality of the data of the very important areas in computer applications , Where many researchers work in the fields of concealment and encryption . So in this research we are working on the combining of the two methods , where confidential data is encrypted by using  a proposed method , Then the cover is encrypted (regular image) by LCG algorithm (which generates a series of random numbers) to generate the encrypted cover (irregular image) , After that ,we hide the encrypted data in encrypted cover by depending on the LSB technique, then we convert the irregular image into regular image and thereby getting  hidden data in random locations in the  cover image  , This method is characterized by flexibility in terms of the possibility of hiding the different  types of confidential data in different types of media , and durability as that data be hidden in random locations and this  what distinguishes the proposed algorithm , and the results showed high security, because the data is hidden in random locations in encrypted image then convert to the original regular image For clarification of the proposed algorithm , it has been applied on a digital image of the gray type using MATLAB language  by using the efficiency scales PSNR and MSE